The Influence of the IMC (Interactive Mathematical Conceptualization) Model with Wayground on the Basic Mathematical Abilities of Elementary Madrasah Students - Choirul Anwar; Suwardi; Win Listyaningrum Arifin; Lilis Setyaningsih (JENIUS (Journal of Education Policy and Elementary Education Issues), 2026)
This study aims to examine the effect of the Interactive Mathematical Conceptualization (IMC) model assisted by Web Wayground on the basic mathematical abilities of elementary madrasah students. Utilizing a quasi-experimental approach with a Nonequivalent Control Group design, this study involved 57 fifth-grade students from a single elementary madrasah, assigned to an experimental group ( = 29) and a control group ( = 28). Data were analyzed using Analysis of Covariance (ANCOVA) with pre-test scores as covariates. The results revealed a significant effect of the IMC model on students' basic mathematical abilities,  (1, 54) = 10.326,  = 0.002, with a Partial Eta Squared () of 0.161, indicating a large practical effect size. The experimental group achieved a higher post-test average (82.06) compared to the control group (71.96). The pedagogical novelty lies in repositioning the digital platform as an initial exploration tool and utilizing real-time interaction data for guided conceptualization, which strengthens Cognitive Load Theory and social constructivism. The study recommends integrating the IMC model to enhance basic mathematical abilities in elementary education, suggesting future research investigate higher-order thinking skills through longitudinal designs.